Randomness and determinism: Why are the planetary orbits elliptical? - Sheynin, Oscar (Silesian Statistical Reviev, 2014)
I consider the interpretation of the notion of randomness in natural science from Aristotle to Poincaré, the interrelation between randomness and necessity according to Poincaré and the narrower understanding of randomness in the theory of probability and statistics. Kepler explained the ellipticity of the planetary orbits by random causes and Kant and Laplace largely followed him in spite of Newton who had established that ellipticities depended on the planets’ velocity
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2014, nr 12 (18), s. 57-74
Keywords: Keplerian laws; planetary orbits; randomness and necessity; spontaneous generation; system of the world